Injection molded of high density 316L stainless steel for bio-applications - (:unkn) unknown (My University, 2011)
High density sintering of austenitic stainless steel such as 316L involves a combination of relatively high temperature (>1350 °C) and extended sintering time. The research was investigated the effect of addition of boron on sintering characteristics of austenitic stainless steel. Addition of boron is promoted to get high density of sintered stainless steels. The amount of boron plays a role in determining the sintered microstructure and all properties. In this study, 316L stainless steel powders have been used with the elemental NiB powders. A feedstock containing 62.5 wt % powders loading was molded at different injection molded temperature. The binders were completely removed from molded components by solvent and thermal debinding at different temperature. The debinded samples were sintered at different temperature for 60 min under high purity H2 atmosphere. Mechanical property, microstructural characterization and electrochemical property of the sintered specimens were performed using tensile testing, hardness, optical, scanning electron microscopy and electrochemical corrosion experiments. The results are compared and analyzed to predict the strength and weakness of the test conditions.